Tinjauan Koreografi Tari Silek Paarakan Di Jorong Kampung Surau Kenegarian Gunung Selasih Kecamatan Pulau Punjung Kabupaten Dharmasraya - Mahdalena Ekaputri; Darmawati Darmawati (FBS Universitas Negeri Padang, 2020)
This research aims to describe and study the form of Choreography Review of Paarakan Silek Dance in Jorong Kampung Surau, Kenegarian Gunung Selasih, PulauPunjung District, Dharmasraya Regency. This is a qualitative research using a descriptive analysis method. The object of this research was Silek Paarakan dance in Jorong Kampung Surau. The main instrument was the researcher itselfand was assisted by stationery and a photo camera. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by collectingand analyzing the data. The results of the research prove that the Choreography Review of Silek Paarakan Dance is a traditional dance in Jorong Kampung Surau. It is especially performed at Maarak Niniak Mamak Ka Rumah Gadang event and is performed once a year after the Eid prayer. The movements of Silek Paarakan dance consist of Sambah Kiri, Sambah Kanan, Mempersilahkan, Manyangua Tingkok, Tampelong, Tupai Bagaluik, Lantiang Pauh, and Ujak Musang movements. The dancers consist of 20 men. The music used is Talempong Pacik Dan Gong. The costumes worn by the dancers include: Taluak Balango black shirts, Endong (itiak palm) pants, Sembat wrapped around the waists, and black caps. The performance is held in an open field (yard) during the day.